Identification and expression analysis of bZIP transcription factors in Setaria italica in response to dehydration stress - Yang, Xuefei; Gao, Changyong; Hu, Yaqian; Ma, Qianru; Li, Zejun; Wang, Jing; Li, Zhaoqun; Zhang, Li; Li, Dongming (Frontiers in Genetics, 2024)
Among the largest transcription factor families in plants, bZIPs are crucial for various developmental and physiological processes, particularly abiotic stress resistance. Setaria italica has become a model for understanding stress resistance mechanisms. In this study, we identified 90 bZIP transcription factors in the S. italica genome. SibZIPs were classified into 13 groups based on references to Arabidopsis bZIPs. Members in the same group shared similar motifs and gene structure pattern. In addition, gene duplication analysis indenfied 37 pairs of segmental duplicated genes and none tandem duplicated genes in S. italica suggesting segmental duplication contributed to the expansion of the S. italica bZIP gene family. Moreover, the number of SibZIPs genes (39) exhibiting higher expression in roots was significantly more than that in other organs. Twelve SibZIP genes were up-regulated in response to dehydration stress. In conclusion, our study advances the current understanding of SibZIP genes and provide a number of candidates for functional analysis of drought tolerance in Setaria italica.